Sistem Pendukung Keputusan Penentuan Kesesuaian Lahan Tanaman Cengkeh Dengan Metode Profile Matching - Dessy Sarah Simbolon; Bosker Sinaga (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Clove is a type of spice plant that has many benefits. The part that is often used from the clove plant is the flower bud. Usually it will go through a drying process before it is finally consumed or used. The method used to determine land suitability for clove plants is the profile matching method. The data used in determining the suitability of land for clove plants was obtained by using observation and interviews with employees at the address of Kuta Galuh Village, Tiga Ndreget District, Karo Regency. The system for determining land suitability for clove plants was built using a web-based programming language and MySQL database. The purpose of this study was to determine the suitability of land for clove plants in Tiga Ndreget District, Karo Regency. Calculation of ranking determination The final result of the profile matching process is ranking. Determination of ranking refers to the results of certain calculations. The results of the calculation of the profile matching method include Kuta Galuh Village with a Final Score of 5.02 Ranking 1, Nari Gunung Village with a Final Score of 4.98 Ranking 2, Tanjung Belang Village with a Final Score of 4.56 Ranking 3.